Assignment 2 for Philosophy 167. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Write a 5 to 7 page paper comparing the evidence available as of 1651 for the law of free fall, the law of parabolic trajectory, and the law of inertia, respectively.